Nacjonalistyczna krytyka demokracji na przykładzie Narodowego Odrodzenia Polski - Kozerska, Ewa; Klimontowska, Julia (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
In the Polish political arena, the National Rebirth of Poland (Narodowe Odrodzenie Polski — NOP) is classified as a national radical group. Its ideological and political identification, referring to the inter-war national tradition, at the level of negative content is focused on contesting the communist regime, but also the order of liberal democracy sanctioned after the ‘round table agreement’ in Poland. In opposition to the above-mentioned and comparably bluntly evaluated systemic solutions, the organisation promotes a peculiar concept of nationalism (‘New State’), which is supposed to constitute the only legitimate systemic alternative as a guarantor of a properly understood Polish national identity and the raison d’état of the state. From this idealistic perspective, using a verbal and sometimes socially unacceptable forceful method of action, NOP seeks to prove the weakness of the democratic system prevailing in Poland. Particularly, at the level of contemporary axiological as well as institutional-legal processes, it perceives a threat to important assumptions of their agenda: traditional national and religious values, subjectivity of the Polish citizen and sovereignty of the national state (mainly in relations to unacceptable EU and NATO structures). In order to achieve the postulated ideological goals, it does not assume (at least at the level of its rhetoric so far) compromises with the prevailing systemic solutions and cooperation with the current political establishment.
Keywords: nacjonalizm; antydemokratyzm; antyliberalizm; suwerenność; Narodowe Odrodzenie Polski